Zombelina - Crow, Kristyn,Idle, Molly (Bloomsbury Publishing USA, 2013)
Cover – Zombelina.
Description based on publisher supplied metadata and other sources
Keywords: Stories in rhyme; Zombies-Fiction; Ballet dancing-Fiction; Electronic books